2017
DOI: 10.17116/oftalma2017133299-103
|View full text |Cite
|
Sign up to set email alerts
|

Atypical clinical case of solar retinopathy

Abstract: The paper presents an atypical case of solar retinopathy after short-term exposure to reflected focused sunbeams. An ophthalmoscopic peculiarity was the presence of intraretinal hemorrhage. The basis for establishing the diagnosis were spectral optical coherence tomography and fluorescein angiography findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
1
Order By: Relevance
“…The OCT scans crossing the central fovea displayed a dot-shaped destruction of the IS/OS and photoreceptor outer segment layer with insubstantial deformation of adjacent retinal layers caused by detritus, which is close to our findings [17]. Pomytkina et al [18] reported a case of unintended retinal damage from reflected sunlight. In that case, a driver presented with complaints of abrupt loss of vision and a spot in his central vision in his left eye after accidentally looking at the sun ray reflected at the side-view mirror.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The OCT scans crossing the central fovea displayed a dot-shaped destruction of the IS/OS and photoreceptor outer segment layer with insubstantial deformation of adjacent retinal layers caused by detritus, which is close to our findings [17]. Pomytkina et al [18] reported a case of unintended retinal damage from reflected sunlight. In that case, a driver presented with complaints of abrupt loss of vision and a spot in his central vision in his left eye after accidentally looking at the sun ray reflected at the side-view mirror.…”
Section: Discussionsupporting
confidence: 90%
“…The retinal OCT changes in the case reported by Pomytkina et al [18], however, were more apparent than in the case reported here.…”
Section: Discussioncontrasting
confidence: 77%